2014
DOI: 10.3352/jeehp.2014.11.23
|View full text |Cite
|
Sign up to set email alerts
|

Student feedback about the integrated curriculum in a Caribbean medical school

Abstract: Purpose:Xavier University School of Medicine adopted an integrated, organ system-based curriculum in January 2013. The present study was aimed at determining students’ perceptions of the integrated curriculum and related assessment methods.Methods:The study was conducted on first- to fourth-semester undergraduate medical students during March 2014. The students were informed of the study and subsequently invited to participate. Focus group discussions were conducted. The curriculum’s level of integration, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…The reason for such better score may be related to the fact that problem-based learning style encouraged group work and active learning among students and made them more recognized for their course material. However, our study's sample size is larger than that study and with a variety of students' levels; it showed no significant differences in the final results of the PBL and traditional learning method [16].…”
Section: Discussioncontrasting
confidence: 57%
“…The reason for such better score may be related to the fact that problem-based learning style encouraged group work and active learning among students and made them more recognized for their course material. However, our study's sample size is larger than that study and with a variety of students' levels; it showed no significant differences in the final results of the PBL and traditional learning method [16].…”
Section: Discussioncontrasting
confidence: 57%
“…While an initial decline in examination scores has been reported following the introduction of multidisciplinary assessments (Moqattash et al, ; McKeown et al, ; Thompson et al, ), some medical educators contend that the integration of content promotes knowledge retention by enhancing the connections within and between content areas (Norman and Schmidt, ). In other instances, students have expressed positive feedback regarding integrated assessments as they collectively assess basic science knowledge in reference to clinical scenarios (Shankar et al, ). In a study on integrated practical examinations, Hudson and Tonkin () suggest that by truly integrating practical examination material, one can further reduce the number of items required per examination.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations have, in turn, affected the achievement of the intended learning outcomes in all domains of Bloom Taxonomy (1,2). Many studies have reported the feedback of the students about the integrated curriculum (3-6) such as Wilkerson et al (3), Shankar et al (4), and Lam et al (5) found that the student feedback was positive for the integrated curriculum, while Thompson et al (6) found no difference between the discipline-specific curriculum and the integrated curriculum. Most of these studies highlighted the positive feedback for the integrated curriculum (7,8), but some of them have reported the disadvantages of the curriculum (9).…”
Section: Introductionmentioning
confidence: 99%